2009
DOI: 10.1002/jsfa.3831
|View full text |Cite
|
Sign up to set email alerts
|

Red clover (Trifolium pratense L.) isoflavones: root phenolic compounds affected by biotic and abiotic stress factors

Abstract: Elevated ozone, cultivation regime and growth stage affected the levels of phenolics in red clover roots, suggesting sensitivity of root phenolics to biotic and abiotic stress conditions. The high levels of phenolics found in roots even in late autumn may be utilised in many applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Isoflavonoids are known to mediate plant-insect interactions, either deterring or stimulating insect feeding behaviour (Simmonds, 2003). For red clover, Saviranta et al, (2010) previously reported that the most abundant phenolic compounds in field-grown roots were the maleate glycoside of formononetin and Superqueli INIA. However, the highest content of formononetin were found in roots of red clover (cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflavonoids are known to mediate plant-insect interactions, either deterring or stimulating insect feeding behaviour (Simmonds, 2003). For red clover, Saviranta et al, (2010) previously reported that the most abundant phenolic compounds in field-grown roots were the maleate glycoside of formononetin and Superqueli INIA. However, the highest content of formononetin were found in roots of red clover (cv.…”
Section: Discussionmentioning
confidence: 99%
“…The differences could be explained by different factors, such as seasonality, environmental and organ or part of plant used for the analysis (Saviranta et al, 2010). On the other hand, Papadopoulus et al, (2006) indicated that there is significant genetic variability for formononetin (2) content among red clover cultivars, and concluded that the selection of individual plant phenotypes for high formononetin (2) could be effective for cultivar improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavonoids and flavonoids are, due to their wide spectrum of biological effects, some of the closely studied secondary metabolites of plants [1, 2]. Their major producers are plants of the legume family (Fabaceae).…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant isoflavonoids in pot-grown roots were formononetin glycoside malonate (G-M) (1.51–4.26 mg g −1  DW), formononetin (2.21–3.57 mg g −1  DW), and biochanin A (1.73–2.17 mg g −1  DW), whereas field-grown roots were rich in formononetin-G-M (3.90–4.27 mg g −1  DW) and pseudobaptigenin-G-M (1.80–2.58 mg g −1  DW). Elevated ozone, cultivation regime, and growth stage affected the levels of phenolics in red clover roots, suggesting sensitivity of root phenolics to biotic and abiotic stress conditions [1]. …”
Section: Introductionmentioning
confidence: 99%
“…A total of 28 phenolic compounds were tentatively identifi ed in red clover roots (Saviranta et al 2010b ). The most abundant phenolics in pot-grown roots were formononetin glycoside malonate (G-M) (1.51-4.26 mg/g), formononetin (2.21-3.57 mg/g) and biochanin A (1.73-2.17 mg/g), whereas fi eld-grown roots were rich in formononetin-G-M (3.90-4.27 mg/g), maackiain-G-M (2.35-3.02 mg/g) and pseudobaptigenin-G-M (1.80-2.58 mg/g).…”
Section: Root Phytochemicalsmentioning
confidence: 99%